Interleukin‐6 receptor alpha and CD27 discriminate intratumoral T helper 17 subpopulations with distinct functional properties in a mouse lung cancer model. Issue 4 (27th September 2021) - Liu, Chong; Xiong, Fei; Wang, Lingying; Chen, Kang; Wu, Pingshang; Hua, Li; Zhang, Zhuo
Abstract: Background: T helper 17 (Th17) cells actively participate in the tumor immune response in lung cancer. However, the heterogeneity and plasticity of intratumoral Th17 cells in lung cancer remain elusive. In this study, Th17 subpopulations were characterized in a mouse lung cancer model. Methods: Urethane was administered to induce lung cancer in interleukin (IL)‐17‐EGFP transgenic mice. Flow cytometry was used to analyze the phenotypes, signaling status, and functions of Th17 subpopulations either in vivo or in vitro. The adoptive transfer assay and real‐time polymerase chain reaction were applied to analyze the plasticity of Th17 subpopulations. Results: IL‐6Rα high CD27 − Th17 and IL‐6Rα low CD27 + Th17 were identified in intratumoral Th17 cells. The two subpopulations expressed equivalent RORγt. However, the former expressed higher T‐bet but lower Foxp3, more IL‐17A and IFN‐γ but less IL‐10 than the latter. Furthermore, IL‐6Rα high CD27 − Th17 moderately inhibited the proliferation of lung cancer cells while IL‐6Rα low CD27 + Th17 could not. IL‐6Rα high CD27 − Th17 exhibited weaker Jun N‐terminal kinases (JNK) signaling but stronger signal transducer and activator of transcription 3 (Stat3) signaling than IL‐6Rα low CD27 + Th17. The adoptive transfer assay indicated that both subpopulations downregulated RORγt in recipients' spleens but maintained RORγt in recipients' lungs. Meanwhile, IL‐6Rα high CD27 − Th17 expressed higher T‐bet and IFN‐γ than IL‐6Rα low CD27 + Th17 in the recipients. IL‐6Rα low CD27 + Th17 expressed Foxp3 and IL‐10 in recipients' spleens but not lungs. Conclusions: This study reveals intratumoral Th17 subpopulations with distinct functional properties and signaling patterns, thus offering valuable insight into Th17 heterogeneity and plasticity in lung cancer. Abstract : IL‐6RαhighCD27 − Th17 and IL‐6RαlowCD27+ Th17 cells differentially express master regulators key to T helper cell polarization, as well as cytokines crucial for tumor immunity.